Design and implement of welding machine for circular welding process - Massaid, Ahmad; Alama, Ahmad; Al-Hashlamoon, Raad (جامعة بوليتكنك فلسطين - كلية الهندسة - ميكانيك, 2019)
Welding process is associated with many factors, these factors affect the rate of production and cost in addition to profit margin. In the manual welding system, welding was done manually using welding pistols, so the weld is not produced with the precision and quality required. The objective of this project is to produce circular welding for cylindrical work pieces more efficiently, higher accuracy, better quality, less running time, fewer workers and better consideration of worker safety. The welding process is achieved by "PLC". This project is about the number of inputs and outputs that have been introduced into the program using control systems. The system is controlled by a programmable logic controller. Automatic welding system produces circular welds independently of workers' skills. ترتبط عملية اللحام بالعديد من العوامل ، تؤثر هذه العوامل على معدل اإلنتاج والتكلفة باإلضافة إلى هامش الربح. في نظام اللحام اليدوي ، كان اللحام يتم يدويًا باستخدام مسدسات اللحام ، لذلك ال يتم انتاج اللحام بالدقة و الجودة المطلوبة . الهدف من هذا المشروع هو إنتاج لحام دائري لقطع الشغل األسطوانية بكفاءة أكبر ودقة أعلى وجودة أفضل ووقت تشغيل أقل وعدد أقل هذا المشروع حول عدد المدخالت ."PLC" من العمال ومراعاة أفضل لسالمة العمال. يتم تحقيق عملية اللحام عن طريق والمخرجات التي تم إدخالها إلى البرنامج باستخدام أنظمة التحكم. يتم التحكم في النظام بواسطة جهاز تحكم منطقي قابل .للبرمجة. النظام اآللي للحام ينتج اللحامات الدائرية بشكل مستقل عن مهارات العمال .
no of pages 99 , ميكانيك 10/2019
Keywords: circular welding process; welding machines